Calibration of surface runoff parameters with the hydrologic tank model using recursive digital filter and master recession curve - Suryoputro, Nugroho; Suhardjono, Suhardjono; Soetopo, Widandi; Suhartanto, Ery (Fakultas Teknik UB, 2019)
There are two basic methods to calibrate the hydrological model: (1) the trial and error procedure; (2) the automatic calibration. The problem in the calibration method is the determination of the initial value of the parameters. This poses a problem for beginner model users. This paper presents the calibration results of surface runoff parameters in the hydrological tank model using recursive digital filter method and the master recession curve. The results indicate that the Recursive Digital Filter as a surface runoff separation method can be used for the initial approach to calibrate the tank model parameters